2015
DOI: 10.1158/1535-7163.mct-15-0188
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anti-TM4SF1 Antibody–Drug Conjugates with Activity against Tumor Cells and Tumor Vasculature

Abstract: Antibody-drug conjugates (ADC) represent a promising therapeutic modality for managing cancer. Here, we report a novel humanized ADC that targets the tetraspanin-like protein TM4SF1. TM4SF1 is highly expressed on the plasma membranes of many human cancer cells and also on the endothelial cells lining tumor blood vessels. TM4SF1 is internalized upon interaction with antibodies. We hypothesized that an ADC against TM4SF1 would inhibit cancer growth directly by killing cancer cells and indirectly by attacking the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 43 publications
(63 reference statements)
0
20
0
Order By: Relevance
“…The initial anti-CD276 ADC we generated used the tubulin binding anti-mitotic drug MMAE, attached to m276 through a cathepsin B cleavable valine-citrulline linker (Figure S3C). We chose vcMMAE because the same drug-linker technology is used in the US FDA-approved brentuximab vedotin and several other ADCs in clinical development, and previous reports suggest that tumor vessels may be particularly sensitive to auristatin-like compounds (Visintin et al, 2015). Upon target binding and internalization the dipeptide linker can be cleaved by lysosomal proteases releasing cell-permeable MMAE which can then freely diffuse into nearby cells in a target-independent manner resulting in substantial bystander killing (Li et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The initial anti-CD276 ADC we generated used the tubulin binding anti-mitotic drug MMAE, attached to m276 through a cathepsin B cleavable valine-citrulline linker (Figure S3C). We chose vcMMAE because the same drug-linker technology is used in the US FDA-approved brentuximab vedotin and several other ADCs in clinical development, and previous reports suggest that tumor vessels may be particularly sensitive to auristatin-like compounds (Visintin et al, 2015). Upon target binding and internalization the dipeptide linker can be cleaved by lysosomal proteases releasing cell-permeable MMAE which can then freely diffuse into nearby cells in a target-independent manner resulting in substantial bystander killing (Li et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that RTN4 was regulated by AR in AIPC; however, its function was not clarified [25]. TM4SF1, originally described as "TAAL6", is a tumor-associated antigen found in various human epithelial malignancies including breast, ovarian, lung, and colon carcinomas [26,27]. Recent studies indicated that TM4SF1 plays a critical role in cancer cell migration and invasion [28]; it was also shown to be an androgen-responsive protein [29].…”
Section: Discussionmentioning
confidence: 99%
“…It plays a critical role in regulating tumor angiogenesis, motility, migration and invasion [ 13 , 14 ]. Importantly, recently study has shown that TM4SF1-targeting Antibody Drug Conjugates represent a promising therapeutic agent against tumor cells and the tumor vasculature [ 15 ]. Thus, the goal of this study was to investigate whether TM4SF1-overexpressing pancreatic cancer cell lines are involving in gemcitabine resistance and to delineate the mechanism.…”
Section: Introductionmentioning
confidence: 99%